Do Relapses Follow ANCA Rises? A Systematic Review and Meta-Analysis on the Value of Serial ANCA Level Evaluation - Al-Soudi, Aram; Vegting, Yosta; Klarenbeek, Paul L.; Hilhorst, Marc L. (Frontiers in Medicine, 2022)
Objectives ANCA-vasculitis (AAV) patients frequently suffer from relapses and risk subsequent organ damage. There is much debate on the value of serial ANCA level evaluation to monitor disease activity. We aimed to evaluate the association between ANCA rises and disease relapses at (I) moment of the rise, (II) within 6 months or (III) within a year from the rise. Methods 3 databases (MEDLINE, EMBASE, COCHRANE) were searched from 1993 through September 2021. We included studies that reported relapse incidence within 12 months after an ANCA rise measured by antigen-specific immunoassays in peripheral blood of AAV patients in remission. Quality assessment was performed using QUADAS-2. Finally, a meta-analysis was carried out to estimate average OR using a random effects model. Results Twenty unique studies were included. The methodological quality was limited due to risk of selection bias. An ANCA rise often preceded a disease relapse within 6 months (OR 3.65, 95% CI 1.66–8.03) and less often within 12 months (OR 2.88, 95% CI 1.21–6.88), while it was not indicative of a concurrent relapse (OR 0.13, 95% CI 0.03–0.53). Once a relapse is diagnosed, ANCA is significantly more often present than not (OR 10.80, 95% CI 3.82–30.55). As expected based on clinical, technical and methodological variability between studies, there was substantial heterogeneity across studies in all analyses (I2 = 70–87%). Conclusion In previously ANCA-positive patients, the ANCA test is often positive upon clinical suspicion of a disease relapse. Patients with a rise in ANCA are at risk of encountering disease relapses in the upcoming 6 or 12 months.